2010
DOI: 10.1021/la100623y
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Catalyzed Synthesis and Triggered Gelation of Ionic Peptides

Abstract: We investigate the possibility of using the protease thermolysin to drive the synthesis and gelation of ionic-complementary peptides from nongelling precursors. In this system, short peptide fragments are continuously interconverted to form a dynamic peptide library, which eventually favors synthesis of peptides that are thermodynamically stabilized by molecular self-assembly. Thermolysin was added at a fixed concentration (0.3 mg mL(-1)) to solutions (0-300 mg mL(-1)) of the short tetrapeptide FEFK. Initially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
89
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 43 publications
2
89
1
Order By: Relevance
“…The oscillatory rheometry test showed that the storage modulus could go up to 25 kPa at 300 mg/mL. 88 The enzyme concentration would not change the composition of the final products, but affected the reaction kinetics and the shear moduli because of a quicker reaction and denser network formed around the enzymes if using a higher enzyme concentration. 89 This method of forming longer ionic peptides and a fibrous hydrogel from initially short, readily prepared and non-gellable peptides shows promise for peptide synthesis and potential for 3D cell culture and cell delivery for tissue engineering.…”
Section: Ionic Interaction-based Hydrogelsmentioning
confidence: 98%
See 1 more Smart Citation
“…The oscillatory rheometry test showed that the storage modulus could go up to 25 kPa at 300 mg/mL. 88 The enzyme concentration would not change the composition of the final products, but affected the reaction kinetics and the shear moduli because of a quicker reaction and denser network formed around the enzymes if using a higher enzyme concentration. 89 This method of forming longer ionic peptides and a fibrous hydrogel from initially short, readily prepared and non-gellable peptides shows promise for peptide synthesis and potential for 3D cell culture and cell delivery for tissue engineering.…”
Section: Ionic Interaction-based Hydrogelsmentioning
confidence: 98%
“…Recently, an enzymatically triggered reverse hydrolysis method was proposed to synthesize self-complementary ionic peptides and in situ formed peptide hydrogel. 88, 89 The general process is illustrated in Fig. 3B.…”
Section: Ionic Interaction-based Hydrogelsmentioning
confidence: 99%
“…Mixing induced, two-component physical hydrogels and enzyme catalyzed self-assembly have also been reported [2427]. Gelation in such systems is achieved through non-covalent, physical crosslinking by secondary forces such as hydrophobic and Van der Waals interactions, as well as ionic and hydrogen bonding [28].…”
Section: Introductionmentioning
confidence: 99%
“…Although this strategy works fairly well in the design of enzyme-triggered molecular assembly into well-defined nanostructures (catalytic reactions occurring on the unassembled molecules), 2326 only limited successes have been reported on the enzyme-induced morphological transitions 27,28 and the specific degradation of self-assembled supramolecular filaments (catalytic reactions affecting the assembled nanostructures). 2934 In the latter cases, it is not clear whether changes in the assembled structures (both morphological transition and nanostructure degradation) stems from the cleavage reactions occurring on the nanostructures, or on the individual, unassembled molecules that leads to dissociation of the assembled structures into cleavable monomers.…”
Section: Introductionmentioning
confidence: 99%